Optimizing Basement Construction Methods - Nguyen Huu Bao (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
The underground part of SSG TOWER includes 4 basements, 4 basements at a height of -13.2m. Combined with the construction of 3m deep foundation, therefore, the minimum excavation depth is required to -16.2m. Due to the construction work in residential area, relatively ground, with large excavation depth and geology of the interaction area (clay layer up to 30m), the options for using diaphragm wall with drilled piles Small area, Laser piles or solier piles to make retaining walls during construction do not have that feature, so the author chooses the option of using reinforced concrete barrette walls for retaining walls during construction and as tunnel walls for this project. The semi-topdown construction method was chosen to ensure safety during construction because the excavation depth of the work is quite large and the geology of this area is quite weak. This measure completely solves the strut system because using the floor structure of the building to support this system has high stability. Limiting the influence of settlement, cracking, and slippage to neighboring works a lot. Fast construction but in return for high technical requirements, high construction costs. Choose diaphragm wall thickness of 1.0m, base depth of 46.6m including standard barrete panels.  The author uses 2D Plaxis simulation to calculate ground stability, stress and displacement, moment, and shear force generated in diaphragm wall during basement construction. The author analyzes using the optimization algorithm to compare and find the suitable solution.